(untitled) (Journal of Atomic and Molecular Sciences, 2011)
The crystal structure, tetragonal distortion, magnetism, electronic structure and pressure response of Mn_2NiAl are calculated by first-principles method based on the density functional theory. The calculations show, the equilibrium structure of Mn_2NiAl in the cubic austenitic phase is the MnMnNiAl structure with Mn atoms occupy A and B sites and two Mn atoms occupy inequivalent positions. In the process of transform 00a0from a cubic to a tetragonal structure, Mn_2NiAl alloys exhibit a stable martensitic phase near c/a = 1.24. In both the austenite and martensite phases, Mn atoms are the main contributors to the magnetism in Mn_2NiAl, Mn_2NiAl alloys show ferrimagnetism due to antiparallel but unbalanced magnetic moments of Mn(A) atom and Mn(B) atom. The direct d-d exchange interactions between Mn(A) atom and Mn(B) atom are weak because of small overlap of d-projected DOS of Mn(A) atom and Mn(B) atom nearby the Fermi level, but the intra-atomic interactions in Mn atoms are strong, this is the reason why the Mn_2NiAl alloys show ferrimagnetism. The findings strongly suggests that Mn_2NiAl alloys would behave like a magnetic shape memory alloy.